Teaching Ethics and Professionalism: A National Survey of Ophthalmology Residency Program Directors - Kretz, Alyssa M.; deSante-Bertkau, Jennifer E.; Boland, Michael V.; Guo, Xinxing; Collins, Megan E. (Journal of Academic Ophthalmology, 2021)
Background While ethics and professionalism are important components of graduate medical education, there is limited data about how ethics and professionalism curricula are taught or assessed in ophthalmology residency programs.Objective This study aimed to determine how U.S. ophthalmology residency programs teach and assess ethics and professionalism and explore trainee preparedness in these areas.Methods Directors from accredited U.S. ophthalmology residency programs completed an online survey about components of programs' ethics and professionalism teaching curricula, strategies for assessing competence, and trainee preparedness in these areas.Results Directors from 55 of 116 programs (46%) responded. The most common ethics and professionalism topics taught were informed consent (38/49, 78%) and risk management and litigation (38/49, 78%), respectively; most programs assessed trainee competence via 360-degree global evaluation (36/48, 75%). While most (46/48, 95%) respondents reported that their trainees were well or very well prepared at the time of graduation, 15 of 48 (31%) had prohibited a trainee from graduating or required remediation prior to graduation due to unethical or unprofessional conduct. Nearly every program (37/48, 98%) thought that it was very important to dedicate curricular time to teaching ethics and professionalism. Overall, 16 of 48 respondents (33%) felt that the time spent teaching these topics was too little.Conclusion Ophthalmology residency program directors recognized the importance of an ethics and professionalism curriculum. However, there was marked variation in teaching and assessment methods. Additional work is necessary to identify optimal strategies for teaching and assessing competence in these areas. In addition, a substantial number of trainees were prohibited from graduating or required remediation due to ethics and professionalism issues, suggesting an impact of unethical and unprofessional behavior on resident attrition.
Keywords: ethics; professionalism; graduate medical education